A randomised pilot trial of perioperative propranolol combined with celecoxib versus standard of care in stage III melanoma: The ProCel study protocol - Katina J. Selvaraj; Diona L. Damian; J. Guy Lyons; James S. Wilmott; Peter M. Ferguson; Michele McGrady; Iris Bartula; Serigne N. Lo; Richard A. Scolyer; Angela L. Ferguson; Robyn P.M. Saw (PLoS ONE, 2026)
In cutaneous melanoma patients, the presence of lymph node or in transit metastasis can be associated with poor survival. Adjuvant treatment with BRAF-MEK inhibitors or immunotherapy is costly and can cause side effects, so there remains a need for safe and inexpensive adjuvant treatments. Beta-blockers can control the pro-inflammatory stress response associated with surgery, and their use may attenuate the risk of melanoma progression. COX-2 may promote melanoma progression by increasing prostaglandin production, so COX-2 inhibition may be beneficial. This randomised controlled trial will be conducted at Royal Prince Alfred Hospital and Melanoma Institute Australia, and will include forty participants aged 18–85 years with nodal and/or in transit metastatic melanoma. Participants will be randomly allocated to receive propranolol combined with celecoxib perioperatively, or surgical management only. The primary objective is to determine the effect of propranolol combined with celecoxib on intra-tumoral immune cell populations and tumour proliferative markers, assessed using imaging mass cytometry. The secondary objectives are to evaluate the safety and tolerability of the combination, as well as its effects on: 1) serum inflammatory markers; 2) quality of life; and 3) recurrence/progression rates. The trial is registered in the Australian New Zealand Clinical Trials Registry (ACTRN12624001353583). Protocol version 1 was submitted to PLOS One in February 2025. The trial is supported by Sydney Cancer Partners with funding from Cancer Institute NSW (Grant ID 2021/CBG0002). The sponsors are Sydney Local Health District and Melanoma Institute Australia.